Impelemtation of Lesson Study Based STEM Learning to Stidents’ Creativity and Concept Mastery Through Joint Project - Widiyanti, Yanti; Arum, Jesy Wailah; Sukenti, Evi; Alfidayani, Alfidayani; Herawati, Desti (Journal of Learning Improvement and Lesson Study, 2022)
The human skeletal system is a complex material to be studied by students, especially for social studies class students who take Biology specialization subjects. This study aims to train students’ creativity and improve students’ mastery of concepts in the joint subtopic of skeletal system material through a STEM approach with a Project Based Learning model based on lesson study. The research method was a weak experiment with a one-shot case study design. The instruments used in this study include multiple choice test instruments and observation sheets. The results showed that students’ creativity was in the good category with mastery of concepts that had passed the minimum KKM limit. This shows that STEM learning with project-based learning helps students to be able to understand the concept of joints through the implemented projects. The planning and implementation of lesson study-based learning also stimulates collaboration between teachers in the field of study to be able to design innovative learning.